The Effects of Mindfulness-Based Therapy and Counseling (MBTC) on Mindfulness, Stress and Depression in Nursing Students - Ananpatiwet, Somdee; Mekhasilp, Ruemonphan; Ponakhon, Vanee (Journal of International Buddhist Studies, 2017)
This one group pretest-posttest quasi-experimental design aimed to compare mindfulness, stress and depression of nursing students, St Theresa International College on participating in Mindfulness-Based Therapy and Counseling (MBTC). The MBTC consisted of 8 worksheets for 12 sessions. Participants are consisted of 92 students of the second-year nursing students in the course of Ethics and Law in Nursing at the first semester of academic year 2016. Research instruments are included with: Philadelphia Mindfulness Scale (PHLMS-Thai)-Awareness; stress inventory; 9q depression questionnaires with Cronbach’s alpha coefficient reliability at .86, .87, and .71, respectively. Data were analyzed by using descriptive statistics and paired-samples t-test. The result revealed that the mean scores of mindfulness was statistically higher in significant than before participating the MBTC Program (t = -3.37, p < .01). However, the mean scores of stress and depression were not statistically significant. The results showed that the practice of MBTC can enhance mindfulness among nursing students. A recommendation for stakeholder of nursing education institutions should promote essential programs to enhance mindfulness for learning efficiency and to decrease negative mental health outcomes in nursing students.